PENERAPAN PENEMPATAN NILAI EIGEN INFINITE SISTEM SINGULAR PADA PENYELESAIAN PERSAMAAN POLINOMIAL MATRIKS BERBENTUK [Es – A] X + B Y = U(s) - Suryowati, Kris; Setyawan, Yudi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
Problem of solvability of polynomial equations and matrix eigenvalue relation to the placement of an infinite state-feedback is important to learn because it deals with the properties of dynamic and static systems. In this case discussed the problem with putting the infinite eigenvalue decomposition of the standard, then the results are applied to problem solving matrix polynomial equations. On eigenvalue placement or placement of the poles, the problem is determining the state feedback matrix K such that det [Es - A + BK] = a ≠ 0, in a and s with each other independent. Singular linear system that has an infinite eigenvalue will be formed in such infinite eigenvalues ​​are placed so that the system has no eigenvalues ​​of infinite state by providing appropriate feedback. Problems on infinite eigenvalue assignment can be attributed to the determination of polynomial equation solution in the form of matrix [Es - A] X + BY = U(s) for a matrix U(s) with detU(s) = a, so that necessary and sufficient conditions of